PENINGKATAN KEMAMPUAN BERBICARA MELALUI METODE BERMAIN PADA ANAK TUNAGRAHITA RINGAN KELAS II DI SLB NEGERI 1 GOWA - Nurul Fadhilah; Dwiyatmi Sulasminah; Usman Usman (JURNAL ORTO DIDAKTIKA, 2024)
This study examines the speaking ability of a child with an intellectual disability class II in SLB Negeri 1 Gowa. The purpose of this research is to find out: 1) the Speaking ability before applying the roleplaying method to intellectual disability children in SLB Negeri 1 Gowa; 2) The speaking ability before applying the role-playing method to children with intellectual disability in class II in SLB Negeri 1 Gowa. Speaking ability when 2) Speaking ability when applying the role-playing method for children with intellectual disability in class II at SLB Negeri 1 Gowa State 1 Gowa; 3) Ability to speak after applying the role-playing method to method for children with intellectual disability in class II at SLB Negeri 1 Gowa. Research approach This research approach is a quantitative approach with a descriptive research type. The subject of this research is a child with an intellectual disability, class II, at SLBN 1 Gowa with the initials MA. The data collection technique used was the speaking ability test. Data analysis using test results before and after treatment, describing the test results before and after treatment. Test results before and after treatment. The results obtained from this study are: 1) The ability to speak in a class II intellectual disability child in SLBN 1Gowa, before applying the role-playing method, is in the very low category; 2) The ability to speak on a child with intellectual disability class II in SLBN 1 low; 2) The ability to speak in a child with a class II disability in SLBN 1 Gowa after applying the role-playing method is in the very high category; 3) There is an increase in the ability to speak in a child with intellectual disability grade II at SLBN 1 Gowa by applying the role-playing method from the very low category increased to a very high category.